Seguridad y salud en el trabajo en la unidad Materno Infantil de la empresa social del estado San Diego de Cereté, 2019 (2020)
In the E.S.E. The San Diego Hospital of the municipality of Cereté - Córdoba carried out the present work which aims to: Prepare an improvement plan in Safety and Health at Work (SST) for the Maternal and Child functional unit of the ESE San Diego de Cereté, through the realization of a DOFA matrix and its respective analysis, in order to comply with Law 1562 of 2012. Materials and methods. a DOFA matrix was used; evidencing the need to intervene in the Maternal and Child functional unit. Results. Opportunities for improvement were found in the OSH actions, for which an improvement plan is prepared that included the realization of a Virtual Learning Object on the report of incidents and accidents at work. Conclusion. The SST is contemplated in the national regulations being mandatory for employers and workers, which seeks to keep the working population free of dangers; This policy is everyone's responsibility in the health institution and requires continuous improvement to promote the health of workers and thus contribute to quality